(untitled) (Scientiae Studia, 2013)
We analyze the transformations of the notion of horizon in modernity through the different uses that it had in scientific works, written between 1440 and 1624, in which there was discussion of the Ptolemaic argument for the view that the behavior of the horizon proves the centrality of the Earth. We show how the concept of horizon represents other fundamental concepts, which characterize the cosmological systems in dispute and their respective senses of reality and observation. We maintain that the study of the conceptual changes that took place historically in the notion of horizon imply taking a new approach to the so-called Scientific Revolution.